Pengaruh Peran Kepala Ruangan Terhadap Kinerja Perawat Dalam Pemberian Asuhan Keperawatan Diruang Rawat Inap - Trimaya Cahya Mulat; Hartaty Hartaty (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
It should not be the case if the general public and the environment are constantly changing, while nursing which is part of the community has not changed in managing the life of the nursing profession. The purpose of knowing the influence of the role of the head of the room on the performance of the nurse in providing nursing care. The research method uses a type of analytic survey research with cross sectional approach. Data were collected using a questionnaire and analyzed using a linear regression test at a significant level p<0.05. Results based on linear regression tests (T test) showed that there was an influence of the role of the head of the room on the performance of implementing nurses in providing nursing care, namely; planning (p = 0.007), organizing (p= 0.005), directing (p = 0.008) and supervision (p = 0.006). Conclusion of planning, organizing, directing, supervising the head of the room on the performance of implementing nurses in providing nursing care. Managerial capacity of the room head in managing nursing services and formulating policies on the selection system in the appointment of competency-based head of space.